Investigation of the TIG Welding Process for Joining AA6082 Alloy Using Grey Relational Analysis - G. Sathish Kumar; M. Ramesh; S. Dinesh; Prabhu Paramasivam; N. Parthipan (Advances in Materials Science and Engineering)
The goal of this project is to find optimization parameters in the TIG weld bead. To ensure the success of this research project, a semiautomatic TIG was developed. Samples are made in a single bead on top of a substrate (base metal) in a horizontal position. Aluminum 6082 is used as the substrate, and AA5356 filler wire with a diameter of 2.4 mm is used as the filler wire. This research project employs argon as the shielding gas. Welding current (A), travel speed (mm/min), and gas flow rate (lit/min) have all been identified as influencing parameters for welding. The Taguchi orthogonal array L9 (Minitab 19) was used to calculate the amount of runoff and analyze the samples. Tensile and hardness tests were performed on the welded samples. According to the test results, as the current value increases, the tensile strength and the hardness values decrease. As a result of this experiment, it is possible to conclude based on grey relational analysis that the best parameters for welding Al 6082 alloy are 150 A of welding current, 200 mm/min of travel speed, and a gas flow rate of 14 lit/min.